SEE: Synchronized Efficient Energy Calculation for Topology Maintenance & Power Saving in Ad Hoc Networks - Santhi Sri, T.; Rajendra Prasad, J.; Kiran Kumar, R. (Arabian journal for science and engineering (2011), 2018)
Dynamic data transmission for ad hoc networks is a significant concept in wireless communication. Some authors have introduced routing algorithms for dynamic data transmission. However, these algorithms have susceptible mobility between the nodes in large and efficient networks. In this context, position-based opportunistic routing (POR)acts as the routing algorithm, which maintains a stateless property on each node when broadcast implementation is done in wireless communication within a time interval. Due to its stateless property, POR appears to consume more energy for maintaining route recovery, backup communication, and virtual destination on node data delivery. In case of this type of communication in ad hoc networks, a synchronization-based efficient energy (SEE) algorithm is further introduced in the proposed work along with the POR protocol. In essence, SEE is a distributed and randomized calculation process, where nodes retain efficiency in local communication by facilitating packet forwarding between intermediate nodes by using backup communication. Without change of network capacity, SEE decreases energy. We also seek to evaluate the computational analysis of the SEE approach in wireless networks. Our experimental outcomes show how effective cooperative communication is possible in wireless network by using a power consumption model that, in turn, expands the scope of network in communication. Additionally, a SEE enhances performance of this model in parameters such as load maintenance, throughput, interpacket delivery ratio, and power consumption in distributed communication networks.